Cyber Sexual Harassment Sebagai Bentuk Kerentanan Viktimisasi Terhadap Perempuan (Studi pada Tiga Korban Pengguna Twitter Inisial DN, NA, dan R) - Tutrianto, Rio; Nizar, Safilla (UIR PRESS, 2021)
On the internet, women are often experinced a verbal and visual cyber sexual harassment. In general, cyber sexual harassment can be defined as sexual harassment in the cyber realm, the form of cyber sexual harassment are vulgar speech, teasing, and gestures that lead to sexual activity. The woman who use Twitter are carries a different risk than men. Through Twitter, women are vulnerable to being victimized by cyber sexual harassment in the form of sexual content. The emergence of vulnerability of cyber sexual harassment victimization on Twitter is due to four factors, namely, space, capable guardians, suitable target, and motivated offenders. The purpose of this study is to determine the emergence of cyber sexual harassment as a form of victimization vulnerability to women. This research uses visual criminology method, which is a method that uses visual devices such as pictures and conducts interviews with related sources. Referring to the theory used by the author, namely Routine Activity Theory and Lifestyle Exposure Theory to see how individuals become victims of crime and provide opportunities for perpetrators to commit crimes.